Contribution of Isfidzhab scholars to the development of islamic culture and science (Journal of Philosophy Culture and Political Science, 2020)
Scientists living in what is now Kazakhstan have made a significant contribution to the developmentof the Hanafi school fiqh in Central Asia. In particular, these are world-famous scientists fromTaraz, Farab, Isfidzhab, Syganak and other cities. Each of them wrote valuable works in various fields ofscience. This article tells about the life, scientific achievements, labor, religious and government positionsof medieval Islamic scholar of Kazakhstan, Ahmad ibn Mansour Al-Isfidzhabi and about otherisfidzhabic scientists and their biographies along with classification. The name and number of works ofAhmad ibn Mansour al-Isfidzhabi are specified considering historical and biographical works. Details areprovided about how much of his works still in the form of manuscripts and in which libraries they arestored. Considering the fact that Ahmad ibn Mansour al-Isfidzhabi lived in the era of the Karakhanids,his relations with the Karakhan rulers and about the religious and political situations at that time are alsodiscussed. The importance of works of Ahmad ibn Mansour al-Isfidzhabi, his place in the Hanafi school,is confirmed by comparative and analytical methods. At the same time, the possibility of using scientist’swork as basis of the Kazakh school of Islamic сultural studies and introduction into scientific circulationwill be discussed.Key words: Culture, law, rule, biography, manuscript.